2010
DOI: 10.1111/j.1365-2966.2009.16227.x
|View full text |Cite
|
Sign up to set email alerts
|

Keck telescope constraint on cosmological variation of the proton-to-electron mass ratio

Abstract: Molecular transitions recently discovered at redshift zabs= 2.059 towards the bright background quasar J2123−0050 are analysed to limit cosmological variation in the proton‐to‐electron mass ratio, μ≡mp/me. Observed with the Keck telescope, the optical echelle spectrum has the highest resolving power and largest number (86) of H2 transitions in such analyses so far. Also, (seven) HD transitions are used for the first time to constrain μ‐variation. These factors, and an analysis employing the fewest possible fre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
191
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(200 citation statements)
references
References 63 publications
6
191
3
Order By: Relevance
“…Column densities are on a log scale in cm −2 . like HD Malec et al 2010) and CO ) have so far been detected in only one or two high-redshift systems.…”
Section: Star Formation and Molecular Hydrogen In Dla Galaxiesmentioning
confidence: 99%
“…Column densities are on a log scale in cm −2 . like HD Malec et al 2010) and CO ) have so far been detected in only one or two high-redshift systems.…”
Section: Star Formation and Molecular Hydrogen In Dla Galaxiesmentioning
confidence: 99%
“…We followed the same procedure as Malec et al (2010) in our HIRES extraction. HIRES_REDUX performs an optimal extraction of the flux and produces a robust, formal statistical error spectrum.…”
Section: Keckmentioning
confidence: 99%
“…Non-zero values of Δμ/μ = −30.5 ± 7.5 ppm, Δμ/μ = −16.5 ± 7.4 ppm (Ivanchik et al 2005), and Δμ/μ = −24 ± 6 ppm (Reinhold et al 2006) found at z = 2.595 (Q 0405-443) and z = 3.025 (Q 0347-383) from the Werner and Lyman bands of H 2 were later refuted by Wendt & Reimers (2008), King et al (2008) and Thompson et al (2009), who used the same optical absorption-line spectra of quasars and restricted changes in μ at the level of |Δμ/μ| < 6 ppm. The third H 2 system at z = 2.059 towards the quasar J2123-0050 also does not show any evidence of cosmological variation in μ: Δμ/μ = −5.6 ± 5.5 stat ± 2.9 sys ppm (Malec et al 2010). More stringent constraints have been obtained at lower redshifts from radio observations of the absorption lines of NH 3 and other molecules: |Δμ/μ| < 1.8 ppm at z = 0.68 , A&A 516, A113 (2010) and |Δμ/μ| < 0.6 ppm at z = 0.89 (Henkel et al 2009).…”
Section: Introductionmentioning
confidence: 99%